Extracorporeal photopheresis as a therapeutic approach for treatment resistant immune-related adverse events in anti-PD-1-treated melanoma patients - Thielmann, Carl Maximilian; Seier, Johanna Andrea; Schielke, Lisa; Albrecht, Lea Jessica; Zimmer, Lisa; Livingstone, Elisabeth; Zaremba, Anne; Lodde, Georg; Dissemond, Joachim; Sondermann, Wiebke; Krefting, Frederik; Tasdogan, Alpaslan; et al. (Frontiers in Immunology, 2025)
BackgroundCheckpoint inhibition induced immune-related adverse events (irAE) may be steroid-dependent or steroid-refractory and are associated with increased morbidity, mortality and potentially compromised anti-tumor immunity. Extracorporeal photopheresis (ECP) has emerged as an alternative for salvage therapy, however, evidence remains scarce.MethodsThis monocenter retrospective study included patients with either irColitis or irHepatitis, who received ECP after failure or dependence on high-dose corticosteroids + infliximab/vedolizumab or mycophenolate mofetil/tacrolimus. Clinical activity was quantified at least weekly (stool frequency for colitis; AST/ALT for hepatitis) and primary endpoint was change in irAE activity over time. Secondary analyses included steroid-sparing, overall safety, and melanoma-specific outcomes. Spearman’s correlation assessed irAE severity reduction.ResultsSix patients were included in this study (irColitis n = 4; irHepatitis n = 2; CTCAE ≥ 3). Extracorporeal photopheresis was started after initial therapy with corticosteroids and immunosuppression was not successful. All ECP cycles included two consecutive treatment days. irAE activity declined promptly after ECP across patients: irColitis showed strong negative correlation with time since ECP (rs range -0.88 to -0.97); irHepatitis displayed parallel ALT/AST declines (rs ≥ -0.92). Corticosteroids were tapered following ECP start with a median corticosteroid reduction across all patients to 25% of baseline dose (IQR: 20.7 - 33.3) by week 4 and to <5% of baseline dose by week 9 (IQR: 1.6 - 4.7). No ECP-related adverse events were observed. Accelerated disease progression was not observed during or after ECP.Conclusions and relevanceThis study of six patients with irColitis or irHepatitis provides evidence that use of ECP is associated with clinical remission and steroid sparing, while demonstrating an excellent safety profile and not compromising disease control. Our data supports the use of ECP as salvage therapy for steroid- and immunosuppression- refractory irAE in cancer patients.